Analisis Laporan Sosial Islam Untuk Kinerja Keuangan Dan Zakat Pada Bank Umum Syariah Indonesia - Fauzan Zaky Rifai; Fifi Kamalia; Ila Novita Anggraini; Agus Eko Sujianto (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to see the effect of disclosure of corporate social responsibility based on Islamic law on financial performance. This study uses a quantitative approach with a sample size of 8 out of 11 Islamic Commercial Banks in Indonesia taken using a purposive sample. The data collection process is carried out by downloading the annual financial statements of Islamic commercial banks from the annual financial statements, information on corporate social responsibility disclosures based on the Islamic Social Reporting (ISR) consists of 38 items, the zakat variable is measured by 2.5% of the profit before taxes, while the financial performance is seen from the value of Return on Assets (ROA) and Return On Equity (ROE) of each company. Path analysis is used to see the direct and indirect relationship of the disclosure of corporate social responsibility based on Islamic Social Reporting to financial performance, where zakat is a mediation. Path analysis shows that the disclosure of corporate social responsibility using ISR has a direct effect on financial performance (P < 0.001; R2 = 0.33), zakat on financial performance also affects financial performance (P < 0.001; R2 = 0.24). So it can be concluded that the disclosure of social responsibility using Islamic Social Reporting and the implementation of zakat in Islamic commercial banks in Indonesia can be used as steps to improve the company's financial performance.